PHARMACOKINETIC STUDY OF OLOPATADINE 10 MG EXTENDED RELEASE TABLET IN COMPARISON WITH OLOPATADINE 5 MG IMMEDIATE RELEASE TABLET IN INDIAN POPULATION - HUSAIN, SAIYED ZEYAUL ABRAR; KHUROO, ARSHAD; MARWAH, AMIT; VOHORA, DIVYA (International Journal of Current Pharmaceutical Research, 2021)
Objective: This study was designed to assess the pharmacokinetics of single dose of olopatadine hydrochloride 10 mg extended release (ER) tablet of Ranbaxy laboratories limited (two test formulations) with two doses of Allelock® 5 mg immediate release (IR) tablets of Kyowa Hakko Kogyo Co. Ltd. (reference formulation R), in healthy, adult, Indian male subjects under fed condition. Methods: Fifteen healthy male volunteers, 26.07±6.62 y in age and 57.17±6.68 kg in body weight, were divided into three groups and received either olopatadine hydrochloride 10 mg ER tablet or two doses of Allelock® 5 mg tablets in each period. Blood samples were taken at predetermined time points and plasma concentrations of olopatadine were monitored by liquid chromatography mass spectrometric (LCMS/MS). Pharmacokinetic (PK) parameters AUC0-t, AUC0-24, AUC0-∞, and Cmax were calculated for olopatadine using WinNonlin. A statistical analysis was performed on PK data using SAS system. Results: The ER formulations showed a similar AUC as compared to the IR formulation and there was no statistically significant difference in AUC of test formulation A and B and reference R. The ratios of AUC0-t, AUC0-24 and AUC0-∞ for A/R were 91.08, 94.90 and 91.32 and for B/R were 89.63, 93.95 and 89.63 respectively. The ER formulations reported a higher Cmax value as compared to IR formulation. The ratios of Cmax for A/R and B/R were 151.09 and 167.96 respectively. But these higher Cmax values did not pose any safety issue as there were no serious adverse events reported during the study. Conclusion: In conclusion, we can say that though the study drugs did not meet the bioequivalence criteria set by regulatory agencies, but this study gave an insight about PK properties of olopatadine extended release formulation and given an idea about effect of smoking on the PK profile of olopatadine which can be studied in future.